Digital Training and Competency Development in Higher Education - Soumia BENCHOUAT; Meriem GHEZAL (Management and Economics Review)
This study analyses the impact of investing in digital training on competency development within Algerian universities, focusing on digital infrastructure, training programs, and digital educational resources. It examines these dimensions for their role in enhancing the administrative staff’s technical, professional, and personal competencies. The research addresses a clear gap in the existing literature, specifically regarding limited evidence on how digital training influences competency development among administrative staff in Algerian higher education institutions. Digital training has become increasingly significant given rapid technological advancements and growing demands for sustainable institutional performance. A descriptive-analytical methodology was employed, and a questionnaire was distributed to a random sample of 50 administrative employees. Although this limited sample size was selected due to logistical and resource constraints and may affect the generalisability of findings, it provides valuable preliminary insights into digital training effectiveness in the studied context. The findings revealed significant positive relationships between investments in digital training and competency development. Digital educational resources had the most decisive impact, significantly improving technical and personal competencies. They were followed closely by training and development programs, which enhanced technical and professional skills. Although positively related, the digital infrastructure showed limited influence. The study recommends that universities, policymakers, and HR departments collaboratively implement an integrated strategy by investing in reliable digital infrastructure, designing specialised digital training programs tailored to staff needs, and expanding digital educational resources through innovative platforms. This strategic integration effectively promotes competency development, enhances institutional performance, and supports sustainable development.